The Impact Of Using The Flipped Learning Strategy On Mathematics Achievement Among Sixth-Grade Primary Students (International Journal of Environmental Sciences, 2025)
This study aimed to investigate the impact of using the flipped learning strategy on the mathematics achievement of sixth-grade female students. The researchers employed a quasi-experimental design, which was appropriate for the nature of the study. The sample consisted of 47 students from Al-Hussan Model Private Schools, who were selected purposefully. The students were divided into two groups: an experimental group and a control group, with both groups undergoing pre- and post-tests. The experimental group was taught using the flipped learning strategy, whereas the control group received instruction through traditional methods. The results indicated that the use of the flipped learning strategy did not have a significant effect on the mathematics achievement of sixth-grade female students.